Makan Roti Buatan Tangan Sendiri: Gereja Indonesia yang Misioner dan Dialogal - Hartiman, Agustinus (Perspektif, 2015)
The Catholic Church of Indonesia has been struggling for a long time to be a self-sufficient Church. For centuries she has been part of Christian mission. The time came when the Pontiff, Pope John XXIII declared and founded the Hierarchy of the Catholic Church of Indonesia in 1961. From that time on, the Catholics of Indonesia (the clergy and the laity) have been working hand in hand to become self-sufficiency. To a certain sense, the Church has reached the objective, particularly in expressing her very identity, namely being missional community. The article argues that the exact way of doing mission in Indonesia context is to be and to live together for the common good of the multicultural society. Therefore, the two qualities of Church in this country, namely missional and dialogical, are primarily characterised the self-sufficient Church of Indonesia.